Targeted Temperature Management for 48 vs 24 Hours and Neurologic Outcome After Out-of-Hospital Cardiac Arrest: A Randomized Clinical Trial - Kirkegaard, Hans (JAMA, 2017)
IMPORTANCE: International resuscitation guidelines recommend targeted temperature management (TTM) at 33°C to 36°C in unconscious patients with out-of-hospital cardiac arrest for at least 24 hours, but the optimal duration of TTM is uncertain. OBJECTIVE: To determine whether TTM at 33°C for 48 hours results in better neurologic outcomes compared with currently recommended, standard, 24-hour TTM. DESIGN, SETTING, AND PARTICIPANTS: This was an international, investigator-initiated, blinded-outcome-assessor, parallel, pragmatic, multicenter, randomized clinical superiority trial in 10 intensive care units (ICUs) at 10 university hospitals in 6 European countries. Three hundred fifty-five adult, unconscious patients with out-of-hospital cardiac arrest were enrolled from February 16, 2013, to June 1, 2016, with final follow-up on December 27, 2016. INTERVENTIONS: Patients were randomized to TTM (33 ± 1°C) for 48 hours (n = 176) or 24 hours (n = 179), followed by gradual rewarming of 0.5°C per hour until reaching 37°C. MAIN OUTCOMES AND MEASURES: The primary outcome was 6-month neurologic outcome, with a Cerebral Performance Categories (CPC) score of 1 or 2 used to define favorable outcome. Secondary outcomes included 6-month mortality, including time to death, the occurrence of adverse events, and intensive care unit resource use. RESULTS: In 355 patients who were randomized (mean age, 60 years; 295 [83%] men), 351 (99%) completed the trial. Of these patients, 69% (120/175) in the 48-hour group had a favorable outcome at 6 months compared with 64% (112/176) in the 24-hour group (difference, 4.9%; 95% CI, −5% to 14.8%; relative risk [RR], 1.08; 95% CI, 0.93-1.25; P = .33). Six-month mortality was 27% (48/175) in the 48-hour group and 34% (60/177) in the 24-hour group (difference, −6.5%; 95% CI, −16.1% to 3.1%; RR, 0.81; 95% CI, 0.59-1.11; P = .19). There was no significant difference in the time to mortality between the 48-hour group and the 24-hour group (hazard ratio, 0.79; 95% CI, 0.54-1.15; P = .22). Adverse events were more common in the 48-hour group (97%) than in the 24-hour group (91%) (difference, 5.6%; 95% CI, 0.6%-10.6%; RR, 1.06; 95% CI, 1.01-1.12; P = .04). The median length of intensive care unit stay (151 vs 117 hours; P < .001), but not hospital stay (11 vs 12 days; P = .50), was longer in the 48-hour group than in the 24-hour group. RESULTS: In 355 patients who were randomized (mean age, 60 years; 295 [83%] men), 351 (99%) completed the trial. More patients in the 48-hour group had a favorable outcome, but this was not statistically significant. Six-month mortality was not different between the groups. Adverse events were more common in the 48-hour group than in the 24-hour group. There was no significant difference in the time to mortality (hazard ratio, 0.79; 95% CI, 0.54-1.15; P = .22). The median length of ICU stay (151 vs 117 hours; P < .001), but not hospital stay (11 vs 12 days; P = .50), was longer in the 48-hour group than in the 24-hour group. [Table: see text] CONCLUSIONS AND RELEVANCE: In unconscious survivors from out-of-hospital cardiac arrest admitted to the ICU, targeted temperature management at 33°C for 48 hours did not significantly improve 6-month neurologic outcome compared with targeted temperature management at 33°C for 24 hours. However, the study may have had limited power to detect clinically important differences, and further research may be warranted. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT01689077